Some rhetorical devices combined with parallelism in English-Vietnamese proverbs - Nguyen, Nhung Thi My; Pham, Hang Thu; Pham, Quynh Thi Huong (Edelweiss Applied Science and Technology, 2025)
This study examines fundamental rhetorical devices in English and Vietnamese proverbs, with a particular focus on parallelism. It analyzes how these devices function and their effectiveness in conveying meaning and cultural values. Through a comparative approach, the research highlights similarities and differences between the two cultures, thereby contributing to a deeper understanding of linguistic diversity. The findings provide valuable resources for teachers, students, and anyone interested in language and culture while also fostering knowledge exchange between communities.